Faktor-Faktor yang Mempengaruhi Produktivitas Kerja Pegawai Dinas Kebudayaan dan Pariwisata Aceh - Sarboini Sarboini; Sutri Yanti (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2018)
This study entitled factors that influence work productivity at the Aceh Culture and Tourism Office. The purpose of this study is to find out what factors influence work productivity including motivation, work discipline and organizational culture at the Aceh Office of Culture and Tourism. The population in this study were employees at the Aceh Office of Culture and Tourism with a total of 209 employees, then the sample collection in this study used the Slovin formula which amounted to 68 respondents. The data analysis method used is multiple linear regression. The results of the study simultaneously motivational variables, work discipline, and organizational culture have a significant effect on work productivity because the calculated F value of 5.752 is greater than the Ftable value of 2.352. Then Ha = accepted and Ho = rejected. Partially the motivation variable has a significant effect on work productivity because the value of tcount of 2.863 is greater than the table of 1.995. Then Ha = accepted and Ho = rejected. Partially the variable work discipline has a significant effect on work productivity because the value of tcount is 2.547 greater than the table of 1.995. Then Ha = accepted and Ho = rejected. Partially organizational culture variables have a significant effect on work productivity, because the value of tcount is 2.569 greater than t table of 1.995. Then Ha = accepted and Ho = rejected. The correlation coefficient (R) shows a value of 0.684 which indicates that the relationship between the independent variable and the dependent variable is positive because it has a value of R> 0.5. The R2 value of 0.734 shows that only 73.4% of the variation of the dependent variable (work productivity) can be explained by variations in the independent variables (motivation, work discipline, and organizational culture) in this study. While the remaining 26.6% is explained by other variables that are not included in research that might affect work productivity.